Preparation methods of cellulose nanocrystal and its application in treatment of environmental pollution: A mini-review - Zhang, Yuzhe; Zhang, Yan; Xu, Wei; Wu, Hao; Shao, Yizi; Han, Xiaogang; Zhou, Man; Gu, Peiyang; Li, Zhongyu (Colloid and interface science communications, 2023)
Cellulose nanocrystals (CNCs) are rod-shaped nanomaterials with the same chemical composition as plant cellulose and can be extracted by physical, chemical, or biological pretreatment from raw materials. To modify the properties of CNCs, esterification, oxidation, and etherification can be further applied to modify the surface of CNCs. In addition to surface modification, graft modification is an approach to significantly alter the properties of CNCs via covalently conjugating cellulose with other polymers with distinct features. After modification, the adsorption performance of CNCs for heavy metal ions (e.g. Pb2+, Cd2+, Cu2+), organic dyes (e.g. methylene blue, crystal violet), and volatile organic compounds (VOCs) can be greatly improved. This review focuses on the preparation and modification methods of CNCs, as well as the adsorption performance of CNCs and CNC composites. [Display omitted] •The preparation methods of CNCs were reviewed, and the advantages and disadvantages of physical and chemical methods were compared.•The advantages of selecting graft modification were highlighted by comprehensive comparison of various modification methods.•The treatment performance of CNCs and its composite materials after graft modification to heavy metal ions, organic dyes and volatile organic pollutants was greatly improved.